Filmmaking and Critical Pedagogy Amongst Youth as Cultural Empowerment in Banyumas, Indonesia - Tri Adi Sumbogo; Nina Mutmainnah (IKAT: The Indonesian Journal of Southeast Asian Studies, 2022)
The local film community run by cultural activists typically conducts several film practices, such as film production, distribution, and exhibition independently. In post-New Order Indonesia, the Banyumas subculture has become an alternative site of struggle for producing critical films against mainstream and commercial films. This study questions how Banyumas cultural activists develop critical learning and nurture an awareness-raising process for local students through filmmaking and how Banyumas’ local film production forms a new culture enacting social change. The authors adopt a qualitative approach with multiple case studies to investigate the phenomenon. The data was obtained by conducting in-depth interviews with cultural activists and the vocational/high school students as a filmmaker, observation, and documentation of the films they produced. This study implements Paulo Freire’s idea of critical pedagogy through collaborative filmmaking performed by Banyumas cultural activists and local young students within a specific cultural and outside-classroom setting. Through collaborative filmmaking, the local subjects interrogate the current sites of power and social roles by encouraging dialogue and problem-posing methods. Using visual media, the practice of empowering local cultural identities finds its embodiment in filmmaking as a process and result. As a living cultural expression, films preserve the local culture, redefine the value of humanism, and raise critical awareness about larger social, political, economic, gender, and cultural issues.